Real-time assessment of exercising maximal mean power and speed in endurance sports: a Garmin connect IQ App - Zignoli, A.; Whitehurst, P. (Sports Engineering, 2025)
This manuscript presents an algorithm for the calculation of the ratio between the real-time maximal mean speed (or power) output and the individual`s historical maximum. The algorithm has been developed using the Garmin Connect IQ SDK, and it runs on compatible devices, such as cycling and running computers. For outdoor running activities, a Kalman Filter (KF) was developed to estimate road gradients and compute `gradient-adjusted speed,` ensuring accurate performance evaluation in varied terrains. Computational times were estimated at ~ 2 ms during cycling and ~ 12 ms during running, depending on whether the KF was active. The application of this simple methodology on a wearable device, combined with the integration with a web-app for data collection and exchange, makes this contribution novel and significant for the field.